Relationship Between Knowledge Level and Family Rules with Adolescent Risk Behavior - Kusariana, Nissa; Dewanti, Nikie Astorina Yunita; Nandini, Nurhasmadiar (Universitas Islam Bandung, 2023)
Health risk behavior emerges due to risk factors within adolescents, family factors, and external factors outside the family. Poor knowledge about risk behavior and parental control may cause adolescents to develop risky behaviors that affect their health. This study aimed to identify the relationship between family factors and knowledge of adolescent risk behavior. It is a cross-sectional study conducted on 271 adolescents aged 17–25 years in Central Java from April to November 2021, taken by random sampling. Data analysis was performed using the chi-square test with a meaning level of 95%. Results show no relationship between knowledge level and adolescent risk behavior (p=0.665), and there was a relationship between family rules and adolescent risk behavior (p=0.001). Family rules significantly prevent adolescent risk behavior; hence, parents must apply family rules to limit teenage behavior, especially in opposite-sex relationships, to avoid sexual risk behavior.